Expressão do fator tecidual (FT) no tumor de Wilms por reação da cadeia da polimerase em tempo real (RT-PCR) - Moreira, Carla Costa (2011)
The Wilms Tumors (WT) is the most frequent renal tumors of children, and although curable, fatal outcomes may occur. A number a genetic alterations have been suggested as associated factors but still, the exact pathogenesis of WT remains to be fully characterized. Tissue factor (TF) is a glycoprotein which happens to be a key receptor for factor VII/VIIa and is the primary initiator of blood coagulation. Also important, TF has been associated with processes that lead to angiogenesis. It is widely expressed among cells and tissues and recent evidences pointed out an important role for TF in cancer progression and metastasis. Recent evidences suggested that TF may have a role in WT since its immunodetection was associated with poor prognosis. In the present investigation the differential expression of TF was assessed in WT using real-time PCR of RNA retrieved from paraffin sections using microdissection. Different histological components of WT - (blastema, epithelial and stromal) were analysed and the results revealed that TF in blastema and epithelial components was upregulated (14.38 and 16.02-fold respectively, P<0.001). Stroma and control non neoplasic tissues expressed similar levels of expression (P>0.05). TF expression in metastatic lesions from WT was also singificantly upregulated compared to non metastatic lesions. Microvessel density was positively correlated with TF expression (r=0.721). As described for other tumors, TF seems to play a role in malignancy or WT. Further investigations are warranted to better understand the pathways by which TF exerts its effects on tumor progression. Noteworthy, pharmacological strategies that aim at controlling angiogenesis through regulation of TF may be very promising